Implementation of the National Public Service Complaint Management System in Policy Complaints and Reporting for the One-Stop Investment and Integrated Service Office of Kotamobagu City - Kadarasi, Mardani; Wawointana, Thelma; Tarore, Steven (Technium Social Sciences Journal, 2025)
This research aims to find out how the implementation of complaint management is carried out by the Policy Complaints and Reporting Division of the Kotamobagu City Investment and One-Stop Integrated Service Office through the National Public Service Complaint Management System (SP4N-Lapor) application. Researchers use a type of qualitative research with descriptive methods and inductive approaches. Data collection techniques through interviews, direct observation, and documentation. The results showed that the effectiveness of the National Public Service Complaint Management System (SP4N-Lapor) application in managing public complaints has been carried out in accordance with the theory, but there are still some shortcomings such as insufficient human resources, lack of infrastructure in the form of special rooms for operators and administrators, slow response and follow-up of complaints by related regional devices, and lack of socialization to the public regarding the existence of the National Public Service Complaint Management System (SP4N-Lapor) complaint application. It is concluded that the implementation of the National Public Service Complaints Management System (SP4N-Lapor) in Kotamobagu City is not effective enough due to external factors from the community and also internal. From the results of the research that has been done, the authors provide. Suggestions, namely further optimizing socialization, training and adding special administrator employees, increasing socialization to the community, facilities and infrastructure to support complaint management, and the Operational Procedure System (SOP).